1991
DOI: 10.1271/bbb1961.55.751
|View full text |Cite
|
Sign up to set email alerts
|

New types of glycolipids from the surface lipids of Nicotiana umbratica.

Abstract: The surface lipids of Nicotiana umbratica contained several varieties of glycolipids. Three types of glucose esters and five types of sucrose esters were isolated and identified from this species. These glycolipids contained short-chain fatty acids such as acetic, methylpropionic, methylbutyric, 3-methylpentanoic, 4-methylpentanoic and methylhexanoic acids. The acetylated positions of each compound were determined by 2-D NMR, using the HMBC technique. The structures of the glucose esters were 1,6-di-O-acetyl-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
1
10
0
1
Order By: Relevance
“…Therefore, together with the evidence that acetate is incorporated intact into the carboxylterminal two carbon atoms of these FAs, it can be concluded that in L. pennellii odd-chain-length n-FAs are derived from the odd-chain-length n3:0 primer. Therefore, even-chain-length normal FAs are likely to be derived from (Shinozaki et al 1991); however, in these GC-experiments ethylacetic acid is obscured by the solvent peak (hexane), and is therefore not accounted for in calculating the mol % fatty acid composition. The mol % distribution for the straight acyl groups in Petunia cv, Falcon Red (P.h.).…”
Section: Analysis Of [U-13 C]thr Incorporationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, together with the evidence that acetate is incorporated intact into the carboxylterminal two carbon atoms of these FAs, it can be concluded that in L. pennellii odd-chain-length n-FAs are derived from the odd-chain-length n3:0 primer. Therefore, even-chain-length normal FAs are likely to be derived from (Shinozaki et al 1991); however, in these GC-experiments ethylacetic acid is obscured by the solvent peak (hexane), and is therefore not accounted for in calculating the mol % fatty acid composition. The mol % distribution for the straight acyl groups in Petunia cv, Falcon Red (P.h.).…”
Section: Analysis Of [U-13 C]thr Incorporationmentioning
confidence: 99%
“…These polyesters are composed of either Glc or Suc to which as many as five or six FAs, respectively, may be esterified (Schumacher, 1970;Severson et al, 1985;King et al, 1986King et al, , 1990Shinozaki et al, 1991;Shapiro et al, 1994).…”
mentioning
confidence: 99%
“…Sucrose esters isolated from cuticular extracts of other Nicotiana species have been suggested to possess only two C 3 to C 8 acyl moieties and may have from one to four acetyl groups on the fructose. In summary, about 19 different structural types (Figure 1) of sucrose esters have been reported for Nicotiana species, and for any sugar type, a series of homologs are found due to differing acyl groups (7)(8)(9)(10)(11)(12)(13)(14). Sucrose esters regardless of their structure present real challenges in terms of isolation, sample preparation, and molecular characterization because the materials are partially esterified with linear and branched fatty acids of variable chain length.…”
Section: Introductionmentioning
confidence: 99%
“…A presença desses aleloquĂ­micos, no acesso selvagem de tomateiro Lycopersicon pennellii 'LA-716', confere resistĂȘncia a um grande nĂșmero de pragas, inclusive Ă quelas consideradas pragas-chave na cultura do tomateiro. Sua presença tambĂ©m foi identificada em outras espĂ©cies do gĂȘnero Lycopersicon, bem como em outros gĂȘneros da famĂ­lia Solanaceae, inclusive Solanum, Nicotiana e Datura (Severson et al, 1985;King et al, 1990;Shinozaki et al, 1991). Esse grupo de fitoquĂ­micos pode atuar de modo a impedir a oviposição e a alimentação ou, ainda, a exercer efeito deletĂ©rio no desenvolvimento de determinadas fases dos artrĂłpodos-praga (Goffreda et al, 1989;Liedl et al, 1995;Resende et al, 2002aResende et al, , 2006Baldin et al, 2005).…”
Section: Introductionunclassified